2005
DOI: 10.1007/s00531-005-0511-2
|View full text |Cite
|
Sign up to set email alerts
|

Contradicting Barrier Reef relationships for Darwin’s Evolution of reef types

Abstract: The Darwinian progressive subsidence model for the evolution of fringing reefs, barrier reefs and atolls has been generally accepted following the indisputable proof of subsidence provided by drilling results in the Pacific. Nonetheless, there are data that do not fit the expectations of the model, such as the similar lagoon depths of barrier reefs and atolls as opposed to the subsidence theory's implicit prediction that atolls should have significantly greater depths. In contrast, a great deal of evidence sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 44 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…This study and preceding drill projects on Bora Bora (Gischler et al ., ; Isaack et al ., ) have shown that Holocene fringing and barrier reefs developed contemporaneously in the same reef system. Comparable results were obtained elsewhere, for example, in the Mayotte (Zinke et al ., ), Chuuk (Truk) and the New Caledonian barrier reef systems (Purdy & Winterer, , and references therein). It is noteworthy in this context that the fringing reef of Bora Bora apparently developed in water depths somewhat shallower as compared to the nearby barrier reef during ca 9 to 5 kyr bp .…”
Section: Discussionmentioning
confidence: 99%
“…This study and preceding drill projects on Bora Bora (Gischler et al ., ; Isaack et al ., ) have shown that Holocene fringing and barrier reefs developed contemporaneously in the same reef system. Comparable results were obtained elsewhere, for example, in the Mayotte (Zinke et al ., ), Chuuk (Truk) and the New Caledonian barrier reef systems (Purdy & Winterer, , and references therein). It is noteworthy in this context that the fringing reef of Bora Bora apparently developed in water depths somewhat shallower as compared to the nearby barrier reef during ca 9 to 5 kyr bp .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been demonstrated repeatedly on both regional and local scales that Pleistocene karst relief provided antecedent topography for Holocene reef formation (e.g., Purdy, 1974ab;Halley et al, 1977;Shinn et al, 1977;Shinn, 1980;Purdy and Winterer, 2006;Hudson, 1998, 2004). More recent treatment of the patterns of reticulate ridges of reefs and sediment in Holocene lagoons has suggested biotic self-organization (Blakeway, 2000;Schlager and Purkis, 2014;Blakeway and Hamblin, 2014), though they may develop also as emergent patterns by interaction of air or water with loose sediment (Paola et al 2009 (Blakeway, 2000;Schlager and Purkis, 2014;Blakeway and Hamblin, 2014).…”
Section: Reticular Reefs In the Recent And Rock Recordmentioning
confidence: 96%
“…Each is discussed in more detail below. Spatial differences in upland drainage size, like those noted for Tahiti (Purdy and Winterer, 2006), are also thought to impact lagoon incision during lowstands; however, western Tahaa catchments are, in general, relatively similar in size to each other.…”
Section: Discussionmentioning
confidence: 96%
“…Backfilling at deltas and deep passes, likely carved by rivers during sea-level lowstands (Fig. 1), are perhaps the most pervasive imprints of fluvial deposition and erosion on reefs, though some have argued that barrier reef morphology itself may be intimately linked to terrestrial drainage networks (Purdy and Winterer, 2006). Makatea islands, which are similar in appearance to uplifted barrier reefs, have been proposed to be modern analogs for how fluvial incision can transform a fringing-reef-bound island into a barrier reef.…”
Section: Introductionmentioning
confidence: 99%